ANALISIS PENYELESAIAN SENGKETA ANTARA PENGANGKUT DENGAN PENGIRIM AKIBAT TERJADI KECELAKAAN - Mila Selvia; Erlina Erlina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Freight forwarding companies function as agents (representatives) in the carriage agreement acting on behalf of the sender or recipient. Freight forwarding companies are regulated in Book I Chapter V Part 2 Articles 86-90 of the Indonesian Commercial Code (KUHD) for rail and water transportation. The results of the research and discussion show that the form of the carriage agreement between PT. Trijaya Sarana Mandiri and the sender is a written agreement in the form of an underhand agreement signed by the parties concerned only. The agreement only binds the parties to the agreement, but does not have the power to bind third parties. In other words, if the agreement is obliged to submit the necessary evidence to prove that the third party's objection is unfounded and cannot be justified. The rights and obligations of the parties between PT. Trijaya Sarana Mandiri and the shipper in a reciprocal carriage agreement, then the obligations of one party are the rights of the other party. According to Law Number 22 of 2009 concerning Road Traffic and Transportation, Articles 186 to 196 explain the rights and obligations of the carrier. How to resolve disputes between PT. Trijaya Sarana Mandiri with the sender due to an accident by taking this non-litigation route, the parties in the future can still establish a good and harmonious relationship, and more importantly, the parties who previously had a dispute in the future are still willing and confident to establish cooperation in the transportation of goods